p-Aminobenzoic Acid-chitosan Conjugates for PABA Delivery to the Large Intestine - Nalinbenjapun, Sirinporn; Ovatlarnporn, Chitchamai (Pakistan Journal of Nutrition, 2016)
Background: The p-aminobenzoic acid (PABA) is an essential nutrient and important substrate for folic biosynthesis in human. The PABA deficiency can cause many symptoms and diseases which may related to folic acid insufficiency. In this study, chitosans with three different molecular weights (30, 80 and 300 kDa) were selected as a macromolecule carrier for the attachment of PABA for pharmaceutical and nutritional applications. Materials and Methods: The first step, amino groups of chitosan were substituted by p-nitrobenzoyl moiety resulting in p-nitrobenzoyl-chitosans (1a-c). The PABA-chitosan conjugates (2a-c) were finally obtained by sodium dithionite reduction process. They were characterized for their functional groups by FT-IR and PABA loading capacity by HPLC. Results: The products of the first step (1a-c) were obtained in good yields (82.49-90.67%) with high purity. The PABA-chitosan conjugates (2a-c) were achieved from the second step also in high yields (82.26-91.86%) and purity. The FT-IR results of 2a-c displayed the C=O stretching, amide II deformation of N-H group and the C-O stretching at 1632.58-1638.00, 1550.08-1559.93 and 1036.58-1040.09 cm–1, respectively. The HPLC results demonstrated that PABA can be loaded onto chitosan in a range of 11.07-23.02% according to the MW of chitosans. Conclusion: These PABA-chitosan conjugates are suitable to delivery PABA to the large intestine and colon where the biodegradation process of chitosan and the cleavage of the attached PABA occur. The released PABA can be utilized as a substrate for folic acid synthesis and for the treatment of PABA deficiency syndrome.